2008
DOI: 10.1016/s0828-282x(08)70688-3
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of chronic coronary artery dissection: Did cisplatin play a role?

Abstract: S pontaneous coronary artery dissection (SCAD) is an unusual cause of acute myocardial ischemia (1). It is more common in younger patients and in women, and has a propensity to affect patients without traditional cardiovascular risk factors (2). The tendency to affect women in high estrogenic states suggests that the hormonal and thrombogenic status of the patient may play etiological roles in SCAD. Similar factors have been implicated in increased cardiovascular event rates observed in young patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Patients with existing cardiovascular pathology have a high risk of this disease [10]. Some cases of myocardial infarction, sudden death and cardiac arrest associated with the capecitabine intake have been described [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with existing cardiovascular pathology have a high risk of this disease [10]. Some cases of myocardial infarction, sudden death and cardiac arrest associated with the capecitabine intake have been described [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous coronary artery dissection has been reported with multiple factors including the peripartum period [ 4 - 5 ], postpartum period [ 6 - 7 ], oral contraceptives use [ 8 ], and connective tissue disorders including Ehlers-Danlos syndrome [ 9 ], systemic lupus erythematosus [ 10 ], neurofibromatosis [ 11 ], sexual intercourse [ 12 ], and bleomycin-etoposide-cisplatin therapy for testicular cancer [ 13 ]. It occurs most commonly in females and the LAD is the vessel affected most often [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin was reported to lead to aortic occlusion in some cases and this impairment was usually irreversible (28,29). In one case, a 36-year-old man who was treated with bleomycin-etoposide-cisplatin therapy for testicular cancer received chronic coronary artery dissection (30). A long-term follow-up in a large cohort of testicular cancer survivors showed that compared with healthy controls, cisplatin-treated patients had, at follow-up, increased systolic blood pressure, increased diastolic blood pressure and a higher prevalence of hypertension (18).…”
Section: Discussionmentioning
confidence: 99%